PENGARUH VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION (STUDI KASUS MAHASISWA UNIVERSITAS ISLAM NEGERI (UIN) SJECH M DJAMIL DJAMBEK BUKITTINGGI) - Indah Fitria Ningsih; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2025)
This research is motivated by the fact that students on campus often spend time monitoring social media so they are easily influenced by the marketing of viral fashion products circulating on social media. The high purchasing power of students for fashion products immediately spreads it quickly to their friends to buy similar products. And in the end there will be excessive consumerism among students. The method used in this research is included in the type of quantitative research. In this research, researchers will reveal the influence of viral marketing on fashion product purchasing decisions among students of the Sharia Business Management Study Program at UIN Sjech M Djamil Djambek Bukittinggi. The results of the research show that there is an influence of viral marketing on the decision to purchase fashion products among students of the Sharia Business Management Study Program at UIN Sjech M Djamil Djambek Bukittinggi. Based on the t test (hypothesis), the significance of the viral marketing variable is 0.000, which is smaller than 0.05 and the t_{calculated} value of 6.631 is greater than t_{table} 1.662, so Ha is accepted and Ho is rejected. It is known that viral marketing has a positive effect on purchasing decisions for fashion products, meaning that every time viral marketing occurs, it will increase students or consumers' decision to purchase fashion products. This is reinforced and supported by the sig value. smaller than the alpha value, namely 0.000 < 0.05, meaning that viral marketing has a positive and significant effect on the decision to purchase fashion products. Next, it can be seen that the results of the calculated t are greater than the t table, namely 6,631 > 1,662, meaning that Ho is rejected and Ha is accepted. So this shows that simultaneously viral marketing among students of the Sharia Business Management study program at UIN Sjech M Djamil Djambek Bukittinggi has a positive and significant influence on the decision to purchase fashion products.